EFEK SUARA PADA KECEPATAN DAN KETERATURAN KERJA - Hartosujono Hartosujono (JURNAL SPIRITS, 2012)
ABSTRACThis Research aim to to know the impact listen the music Mozart to make-up of speed and regularity work. All subjek research as many as 14 people, they were asked to listen the periodical music Mozart, after some times, the performance for the speed of its job regularity and evaluated by using test Kraeplin.Result obtained there no make-up of speed and regularity work, after listening periodical music Mozart. Measurement done at a group of student, with the treatment gift listen the Mozart song for a certain duration, after receiving the the treatment they measured again its performanceCause there no effect of music Mozart at a speed of and this regularity, can be caused, first, all adolescent less hanker to classic music, because them have owned the different music enthusiasm orientation music. Second, lack of kontinuitas time of all subjek to more intensive listen the music MozartKeyword: music Mozart, speed work the, regularity work